Social Policy in the European Sustainable Development Strategy - Ciżmowska, Aleksandra (Problemy Ekorozwoju, 2012)
Sustainable development not only refers to the relationship between the economy and the environment, but it also has a social dimension. This article reviews the original acts and basic documents concerning EU’s sustainable development strategy, from the Maastricht Treaty in 1992 to the latest Europe 2020 (2010) economic strategy, in terms of their reference to the problems of social security and social policy. It also presents examples of EU’s activities in the social pillar of the sustainable development policy, especially in the areas of health, demographic problems, poverty, and social exclusion. A system of indicators is presented as the measure of progress of sustainable development within the Communities. In the final part of this article the system of indicators for health is presented.